Virulence of Jordanian indigenous Beauveria bassiana isolates as entomopathogenic fungi against red palm weevil, Rhynchophorus ferrugineus (Olivier) (Coleoptera: Curculionidae) - Leena A. Irshaid; Mais A. Sweiss; Hazem S. Hasan; Hassan F. Dahi; Heba A. Al-Awaisheh; Danea A. Al-Rajabi (Egyptian Journal of Biological Pest Control)
Abstract Background Red palm weevil (RPW), Rhynchophorus ferrugineus (Olivier) (Coleoptera: Curculionidae), has recently become a significant threat to date palm trees in Jordan and other regions around the world. This destructive pest causes significant economic losses by boring into palm trunks, leading to tree death. Among the different pest management methods within integrated pest management (IPM) programs, biological control utilizing microorganisms has emerged as a promising sustainable approach. Of particular interest is the entomopathogenic fungus Beauveria bassiana which has shown significant efficacy against various insect pests and could be promising. Results Three local isolates of B. bassiana were obtained from soil samples in the Al-Balqa governorate, Jordan. These isolates were identified using morphological and molecular techniques. The virulence of these isolates against RPW larvae and adults was evaluated under laboratory conditions, with isolate BA1 approved to be the most effective, causing 100% mortality rates of wax moth larvae and 90% in RPW larvae, with about 60% mortality of RPW adults. Comparative studies underscored the variability in virulence among different B. bassiana isolates which were influenced by factors such as hydrophobicity and enzymatic activity. Conclusions The findings suggest that local B. bassiana isolates hold potential as an environmentally safe strategy for IPM in date palm cultivation, contributing to sustainable pest control practices for RPW.